Public administration and governance how do they affect government efficiency and effectiveness - Sto. Tomas, Patricia A. (2006)
The pledge of a better and a more responsive government is not new in Philippine public administration. Improving government performance has always been in the agenda of every administration. Ironically, the results of their efforts fell short of expectations. The civil service continues to suffer from the stigma of a negative image as it is commonly described as inefficient, ineffective and corrupt. It is in the context that the initiatives of the public sector in promoting good governance such as the inclusion of good governance in the government agenda, providing organizational mechanisms for reforms, combating corruption, increased participation of the private sector and civil society and improving efficiency, effectiveness, and economy are discussed. How the government adheres to the Asian Development Bank's key principles of sound development management--accountability, participation, predictability, and transparency and World Bank's six dimensions of governance--voice, and accountability, political stability, government effectiveness, regulatory quality, rule of law, and control of corruption is also looked into. Good governance requires honest-to-goodness transformation of the Philippine bureaucracy in a manner that it will be able to efficiently and effectively carry out its functions, while fostering an enabling environment for private sector building and meaning partnership with the civil society.
Keywords: Corruption -- Government policy; Democracy; Governance; Public administration